ANALISIS TRADISI KRAPAN SAPI SEBAGAI BAHAN AJAR FISIKA DI SMA PADA MATERI GERAK LURUS BERUBAH BERATURAN BERBASIS KEARIFAN LOKAL (ETNOSAINS) - Safina Aulia Sani; Sri Astutik; Zhahrotun Nurroniah; Rike Dwi Wulandari; Nurul Faradilla (Jurnal Ilmiah Wahana Pendidikan, 2023)
Karapan Sapi tradition is one of the cultures in Indonesia that can be reviewed from physics phenomena. This study aims to analyze the tradition of Karapan Sapi as a physics teaching material on the material of straight line motion (GLBB). The research method used is the literature review method. The type of method used is systematic mapping study, the writing is done systematically and using predetermined steps. Through this local wisdom-based physics learning can foster the character of students in preserving culture and knowing physics phenomena in everyday life.